PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Yoska Junior Gunawan; Viriany Viriany (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to determine whether firm value can be influenced by profitability, liquidity, leverage, and firm size in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample was selected by purposive sampling method and there were 76 companies that met the criteria. In this study, the data is inputted and then calculated using the Microsoft Excel program and processed using the Eviews 10 program. The results of this study explain that profitability significantly and positively affects firm value, while liquidity, leverage, and firm size have a negative but not significant effect on firm value. company.